The Influence of (R)- and (S)-Warfarin, Vitamin K and Vitamin K Epoxide upon Warfarin Anticoagulation - Kamali, Farhad; Edwards, Clive; Butler, Timothy J.; Wynne, Hilary A. (Thrombosis and Haemostasis, 2000)
The contribution of (R)and (S)-warfarin enantiomers, vitamin K and vitamin K epoxide and patient factors to inter-individual variability in daily warfarin requirements were examined in a group of 73 patients. Simple correlation analysis showed a significant positive relationship between INR values and plasma (S)-warfarin concentrations (r = 0.25; p = 0.038). Multivariate analysis for relationships with INR demonstrated a highly significant positive relationship between INR and (S)- warfarin (p = 0.004) and plasma vitamin K epoxide concentrations (p = 0.028), and a significant negative relationship between INR and plasma vitamin K concentrations (p = 0.034). Twenty five percent of variation in INR could be explained by these variables (adjusted R2 = 0.25). Correlation analysis of data showed that warfarin dosage was significantly and negatively correlated with patient age (r = −0.42; p <0.0001). Patient age accounted for 25% of variation in warfarin dosage requirements (R2 = 0.25). The combined effects of age and vitamin K appear to account for much of the inter-individual variability in warfarin dosage requirements.
Keywords: Warfarin; anticoagulation; vitamin K; vitamin K epoxide; ageing